The Current State and Forecast of Food Production During the Industrial and Innovative Development of Kazakhstan - KAMENOVA, Mazken Zh.; NAKIPOVA, Gulmira N.; AKHMETOVA, Kulianda A.; TERZHANOVA, Aygul Zh.-T.; TAUBAEV, Ayapbergen A.; OMAROVA, Aynura T. (Journal of Advanced Research in Law and Economics; Vol 7 No 3 (2016): JARLE, Volume VII, Issue 3(17), Summer 2016, 2016)
The paper presents the results of theoretical and practical studies regarding the development of the food market in Kazakhstan. Particular attention is paid to the analysis of the current state of the food industry; the necessity of its modernization is substantiated as a condition for ensuring food security, which is an integral part of national security and a prerequisite for the sustainable development of the entire economy of Kazakhstan. The research investigated the factors that affect the development of the industry, including the state of the agro-industrial complex and its main constituent – agriculture, as the main source of raw materials for processing facilities, and the problems in the system of management and state support of the agro-industrial complex branches. The ratios of export, import and Kazakhstan’s percentage in terms of a number of crucial food products was analyzed based on the investigation of statistical material. A forecast of the development of food production in Kazakhstan was made using extrapolation of discovered trends. The obtained forecast data show that the persistence of existing trends will not change the state of the industry significantly. It is necessary to improve management and take measures for developing entrepreneurship in the food industry, which is possible only with reasonable state regulation and maintenance of the balance of interests of agricultural producers and processers.